Aprepitant limits in vivo neuroinflammatory responses in a rhesus model of Lyme neuroborreliosis. Issue 1 (December 2017) - Martinez, Alejandra; Burmeister, Amanda; Ramesh, Geeta; Doyle-Meyers, Lara; Marriott, Ian; Philipp, Mario
Abstract Background Substance P (SP) is produced at high levels in the central nervous system (CNS), and its target receptor, neurokinin 1 receptor (NK-1R), is expressed by glia and leukocytes. This tachykinin functions to exacerbate inflammatory responses at peripheral sites. Moreover, SP/NK-1R interactions have recently been associated with severe neuroinflammation and neuronal damage. We have previously demonstrated that NK-1R antagonists can limit neuroinflammatory damage in a mouse model of bacterial meningitis. Furthermore, we have since shown that these agents can attenuateBorrelia burgdorferi -induced neuronal and glial inflammatory mediator production in non-human primate brain explants and isolated neuronal cells. Methods In the present study, we have assessed the role played by endogenous SP/NK-1R interactions in damaging CNS inflammation in an established rhesus macaque model that faithfully reproduces the key clinical features of Lyme neuroborreliosis, using the specific NK-1R antagonist, aprepitant. We have utilized multiplex ELISA to quantify immune mediator levels in cerebrospinal fluid, and RT-PCR and immunoblot analyses to quantify cytokine and NK-1R expression, respectively, in brain cortex, dorsal root ganglia, and spinal cord tissues. In addition, we have assessed astrocyte number/activation status in brain cortical tissue by immunofluorescence staining and confocal microscopy. Results We demonstrate that aprepitant treatment attenuatesB. burgdorferi -induced elevations in CCL2, CXCL13, IL-17A, and IL-6 gene expression in dorsal root ganglia, spinal cord, and/or cerebrospinal fluid of rhesus macaques at 2 to 4 weeks following intrathecal infection. In addition, we demonstrate that this selective NK-1R antagonist also prevents increases in total cortical brain NK-1R expression and decreases in the expression of the astrocyte marker, glial fibrillary acidic protein, associated withB. burgdorferi infection. Conclusions The ability of a centrally acting NK-1R inhibitor to attenuateB. burgdorferi -associated neuroinflammatory responses and sequelae raises the intriguing possibility that such FDA-approved agents could be repurposed for use as an adjunctive therapy for the treatment of bacterial CNS infections.